2009
DOI: 10.1152/jn.91179.2008
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor-Activated Neurons of the Cat. I. Serotonergic Innervation and Co-Localization of 5-HT7, 5-HT2A, and 5-HT1A Receptors in the Thoraco-Lumbar Spinal Cord

Abstract: Monoamines are strong modulators and/or activators of spinal locomotor networks. Thus monoaminergic fibers likely contact neurons involved in generating locomotion. The aim of the present study was to investigate the serotonergic innervation of locomotor-activated neurons within the thoraco-lumbar spinal cord following induction of hindlimb locomotion. This was determined by immunohistochemical co-localization of serotonin (5-HT) fibers or 5-HT(7)/5-HT2A/5-HT1A receptors with cells expressing the activity-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 120 publications
6
80
1
1
Order By: Relevance
“…Taken together, these results are consistent with recent findings that showed the localization of 5HT1A, 5TH2A, and 5HT7 receptors onto specific and common locomotor-activated neurons with distinct densities along the rostrocaudal extent of the lumbosacral spinal cord (Noga et al, 2009). Thus, these findings reinforce the viewpoint (Hochman et al, 2001; Grillner, 2006; Jordan et al, 2008; Courtine et al, 2009; Hagglund et al, 2010) that descending monoaminergic systems orchestrate the parallel modulation of a widely distributed and heterogeneous, but highly integrated and synergistic, system of circuits that can generate a range of specific gait patterns when recruited in different combinations (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, these results are consistent with recent findings that showed the localization of 5HT1A, 5TH2A, and 5HT7 receptors onto specific and common locomotor-activated neurons with distinct densities along the rostrocaudal extent of the lumbosacral spinal cord (Noga et al, 2009). Thus, these findings reinforce the viewpoint (Hochman et al, 2001; Grillner, 2006; Jordan et al, 2008; Courtine et al, 2009; Hagglund et al, 2010) that descending monoaminergic systems orchestrate the parallel modulation of a widely distributed and heterogeneous, but highly integrated and synergistic, system of circuits that can generate a range of specific gait patterns when recruited in different combinations (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…8A), but the extent of this modulation was lesser than expected (Liu et al, 2009). This general facilitation of rhythmicity, coordination and flexion is consistent with in vitro electrophysiological studies (Liu and Jordan, 2005) and immunohistochemistry analyses (Noga et al, 2009) that demonstrated the preferential localization of locomotor-related 5HT1A and 5HT7 receptors in upper lumbar segments where it has been suggested that the primary circuitry to drive locomotor outputs is located (Kiehn, 2006), and which essentially contain flexor motoneurons.…”
Section: Discussionsupporting
confidence: 84%
“…The immediate early gene cfos is rapidly expressed in neurons in response to stimulation (Morgan and Curran, 1991) and cFos-ir is a marker of transynaptic neuronal activation (Luckman et al, 1994). This approach has been used widely as an indicator of neuronal excitation in the cat and rat spinal cord (Ahn et al, 2006; Ichiyama et al, 2008; Noga et al, 2009). We found cFos-ir neurons in the intermediate gray adjacent to the PNG-spinal cord interface (Figure 7) indicating synaptic activation through connections made with regenerated axons.…”
Section: Resultsmentioning
confidence: 99%
“…However, dual immunohistochemical experiments recently showed locomotor activity-labeled (c-fos) 5-HT1A-, 5-HT2A- or 5-HT7- positive neurons in the cat lumbar cord (specifically in laminae VII-VIII, Noga et al, 2009) suggesting that some of the locomotor activity-related receptors identified recently in in vivo models may indeed be located on CPG neurons (Hochman et al, 2012). …”
Section: Pharmacological and Electrophysiological Properties Of The Lmentioning
confidence: 99%